Avaliação de projetos de pesquisa e desenvolvimento de novos fármacos via opções reais - Rodrigues, Ana Flávia Paiva (2012)
Classical methods for project valuation are based on discounted cash flows at a risk adjusted rate. In what concerns research and development of new drugs, it results that these methods undervalue the project since technical/managerial flexibility along the project lifetime is not taken in account. In view of this, it is proposed to apply the real options theory - according Copeland and Antikarov’s approach - to valuate such projects. Several specialized research articles, reports and panels particularly those ones authored by DiMasi and collaborators (2002, 2003) were used for modeling pharmaceutical R&D costs and revenues. It follows that incorporating management decisions as well as the private risks of the project to the analysis yields a remarkably higher net present value.